Exploring the Use of an Emancipation Checklist for Older Youth (18‐21) Exiting Foster Care. (1st December 2018) - Summers, Alicia; Shdaimah, Corey; Knoche, Victoria A.
Abstract: This paper examines the efforts of a court to improve outcomes for older youth who are exiting foster care by implementing an Emancipation Checklist (EC) to guide discussion around 12 stability indicators thought to improve youth transition to adulthood (e.g., education, employment). Over 90% of youth had medical insurance, all personal documents, a permanent connection, and could identify their core values. Less than half were employed or engaged in educational or vocational training. Youth who exited when they were older and who attended more of their court hearings had more stability indicators. Implications and future research directions are discussed.